Monoclinic phase transformation and mechanical durability of zirconia ceramic after fatigue and autoclave aging - Mota, Yasmine A.; Cotes, Caroline [UNESP]; Carvalho, Rodrigo F. [UNESP]; Machado, João P.B.; Leite, Fabíola P.P.; Souza, Rodrigo O.A.; Özcan, Mutlu (Wiley, 2017)
Objectives: This study evaluated the influence of two aging procedures on the biaxial flexural strength of yttria-stabilized tetragonal zirconia ceramics. Material and methods. Disc-shaped zirconia specimens and (ZE: E.max ZirCAD, Ivoclar; ZT: Zirkon Translucent, Zirkonzahn) (N = 80) (∅:12 mm; thickness:1.2 mm, ISO 6872) were prepared and randomly divided into four groups (n = 10 per group) according to the aging procedures: C: Control, no aging; M: mechanical cycling (2 × 106 cycles/3.8 Hz/200 N); AUT: Aging in autoclave at 134°C, 2 bar for 24 h; AUT + M: Autoclave aging followed by mechanical cycling. After aging, the transformed monoclinic zirconia (%) were evaluated using X-ray diffraction and surface roughness was measured using atomic force microscopy. The average grain size was measured by scanning electron microscopy and the specimens were submitted to biaxial flexural strength testing (1 mm/min, 1000 kgf in water). Data (MPa) were statistically analyzed using 2-way analysis of variance and Tukey's test (α = 0.05). Results. Aging procedures significantly affected (p = 0.000) the flexural strength data but the effect of zirconia type was not significant (p = 0.657). AUTZT (936.4 ± 120.9b) and AUT + MZE (867.2 ± 49.3b) groups presented significantly higher values (p < 0.05) of flexural strength than those of the control groups (CZT: 716.5 ± 185.7a; CZE: 779.9 ± 114a) (Tukey's test). The monoclinic phase percentage (%) was higher for AUTZE (71), AUTZT (66), AUT + MZE (71), and AUT + MZM (66) compared to the C groups (ZE:0; ZT:0). Surface roughness (µm) was higher for AUTZE (0.09), AUTZT (0.08), AUT + MZE (0.09 µm), and AUT + MZT (0.09 µm) than those of other groups. Conclusions. Regardless of the zirconia type, autoclave aging alone or with mechanical aging increased the flexure strength but also induced higher transformation from tetragonal to monoclinic phase in both zirconia materials tested. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1972–1977, 2017.
Keywords: aging; flexural strength; mechanical cycling; phase transformation; yttria-stabilized tetragonal zirconia